Arabidopsis Myosins XI1, XI2, and XIK Are Crucial for Gravity-Induced Bending of Inflorescence Stems - Talts, Kristiina; Ilau, Birger; Ojangu, Eve-Ly; Tanner, Krista; Peremyslov, Valera V.; Dolja, Valerian V.; Truve, Erkki; Paves, Heiti (Frontiers in Plant Science, 2016)
Myosins and actin filaments in the actomyosin system act in concert in regulating cell structure and dynamics and are also assumed to contribute to plant gravitropic response. To investigate the role of the actomyosin system in the inflorescence stem gravitropism, we used single and multiple mutants affecting each of the 17 Arabidopsis myosins of class VIII and XI. We show that class XI but not class VIII myosins are required for stem gravitropism. Simultaneous loss of function of myosins XI1, XI2 and XIK leads to impaired gravitropic bending that is correlated with altered growth, stiffness and insufficient sedimentation of gravity sensing amyloplasts in stem endodermal cells. The gravitropic defect of the corresponding triple mutant xi1 xi2 xik could be rescued by stable expression of the functional XIK:YFP in the mutant background, indicating a role of class XI myosins in this process. Altogether, our results emphasize the critical contributions of myosins XI in stem gravitropism of Arabidopsis.